Pengembangan Aplikasi Pembelajaran Literasi Dasar Siswa Kelas 1 SD Berbasis 2D - Wardana, Ali; Armin, Aidil Primasetya (Penerbit Goodwood, 2025)
Purpose: This study aimed to design and develop a multimedia-based 2D application to improve basic literacy skills for first-grade elementary school students. Methodology/approach: The application, named Petualangan Literasi, was developed using the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, material collection, assembly, testing, and distribution. The research was conducted at SDN Ngingasrembyong using the Unity and C# programming languages. Results/findings: The results showed that the application effectively improved students’ literacy performance. Of the 25 students, five achieved maximum scores, and the majority showed increased performance compared to conventional methods. Conclutions: The study concludes that the 2D multimedia-based application Petualangan Literasi, developed using the MDLC method, is effective in enhancing basic literacy skills among first-grade elementary school students. It provides an engaging, interactive alternative to conventional learning methods, increasing students’ motivation and performance in early literacy education. Limitations: The study was limited to material from Chapter 1 of the 2021 Bahasa Indonesia curriculum and tested on a small sample of first-grade students. Contribution: This research contributes to the field of educational technology by offering an interactive solution for early literacy learning through game-based multimedia applications tailored to young learners.